Foliar selenium application for improving drought tolerance of sesame (Sesamum indicum L.) - Thuc Le Vinh (De Gruyter, 2021)
Drought is the main constraint for crop growth worldwide. Selenium reportedly plays an important role in improving plant tolerance to drought stress. In this study, two experiments were conducted to investigate the effects of foliar selenium application on the drought tolerance of sesame. Five selenium concentrations (0, 5, 10, 20, and 40 mg/L) were used in the first experiment. Water deficit was triggered 25 days after sowing. The application of 5 or 10 mg/L of selenium maintained the number of leaves and increased the number of capsules. However, higher concentrations induced necrosis. The second experiment aimed to study the effect of selenium concentrations (5 and 10 mg/L) and the number of applications (one to three times). Drought stress was triggered 50 days after sowing, and selenium was sprayed 50, 55, and 60 days after sowing. The results indicated that a one-time foliar selenium application of 5 mg/L was able to maintain the number of leaves and to increase proline accumulation, plant biomass, and grain weight per plant. This finding confirms that selenium can be applied to enhance sesame’s tolerance to drought stress.